Phonetic realization of English lexical stress by native (L1) Bengali speakers compared to native (L1) English speakers. (January 2018) - Saha, Shambhu Nath; Mandal, Shyamal Kumar Das
Highlights: Compares the use of acoustic correlates in the production of English lexical stress by English and Bengali speakers. Bengali speakers able to approximate English like patterns of duration, intensity, F0 of stressed and unstressed vowels. It is very difficult for Bengali speakers to acquire acoustic correlate of vowel quality associated with the production of English lexical stress. Bengali speakers' production of English lexical stress contrast is influenced by native language experience and native phonology. Abstract: English lexical stress is acoustically related to combination of duration, intensity, fundamental frequency (F0 ) and vowel quality. At phonetic level, the current study investigates L1 Bengali speakers' acoustic manipulation of English lexical stress to produce English lexical stress contrast. This study compares the use of these correlates in the production of English lexical stress contrasts by 10 L1 English and 20 L1 Bengali speakers. The result showed that, although L1 Bengali speakers did use all four acoustic correlates to distinguish stressed from unstressed syllables, they produced significantly less native-like stress patterns. In particular, there was a significant difference in formant patterns across speaker groups, where L1 Bengali speakers produced English like vowel reduction in some unstressed syllables, but in other cases, L1 Bengali speakers had tendency to either not reduce or incorrectly reduce vowels in unstressed syllables. The results suggest that L1 Bengali speakers' production of English lexical stress contrast is influenced by L1 language experience and L1 phonology.